2018
DOI: 10.3389/fnint.2018.00056
|View full text |Cite
|
Sign up to set email alerts
|

Population Coding and Correlated Variability in Electrosensory Pathways

Abstract: The fact that perception and behavior depend on the simultaneous and coordinated activity of neural populations is well established. Understanding encoding through neuronal population activity is however complicated by the statistical dependencies between the activities of neurons, which can be present in terms of both their mean (signal correlations) and their response variability (noise correlations). Here, we review the state of knowledge regarding population coding and the influence of correlated variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 124 publications
(200 reference statements)
1
9
0
Order By: Relevance
“…We hypothesize that this is because the signal and stimulus-induced noise considered here are "global" because they recruit most if not all of the pyramidal neuron population. Previous studies have shown that noise correlation magnitude is reduced when "global" stimuli are presented 63,65 , which supports our hypothesis. It is nevertheless important to point out that noise correlations are likely to have a much stronger impact on the coding of other behaviorally relevant stimuli, such as those caused by prey.…”
Section: Impact Of Neural Heterogeneities On Population Coding Of Behsupporting
confidence: 91%
“…We hypothesize that this is because the signal and stimulus-induced noise considered here are "global" because they recruit most if not all of the pyramidal neuron population. Previous studies have shown that noise correlation magnitude is reduced when "global" stimuli are presented 63,65 , which supports our hypothesis. It is nevertheless important to point out that noise correlations are likely to have a much stronger impact on the coding of other behaviorally relevant stimuli, such as those caused by prey.…”
Section: Impact Of Neural Heterogeneities On Population Coding Of Behsupporting
confidence: 91%
“…Future studies are needed to investigate how electrosensory neuronal populations encode other natural electrocommunication signals not considered here. In particular, it will be important to consider the fact that ELL PCell trial-to-trial variabilities to repeated stimulus presentations are correlated (Chacron and Bastian, 2008;Simmonds and Chacron, 2015;Hofmann and Chacron, 2018), which has been ignored by previous studies (Marsat et al, 2009;Marsat and Maler, 2010;Allen and Marsat, 2018). Such "noise" correlations can have profound influence on coding by neuronal populations (Averbeck et al, 2006;Cohen and Kohn, 2011;Doiron et al, 2016;Franke et al, 2016;Zylberberg et al, 2016) and are likely to be found in all ELL PCells as they are due to shared input from peripheral afferents Chacron, 2017, 2018).…”
Section: Feature Invariant Representations Of Natural Electrocommunicmentioning
confidence: 99%
“…The sensory feedback that electric fish perceive as they move through their environment depends on the physical structure of nearby objects (Babineau et al, 2007; Hofmann et al, 2014; Dangelmayer et al, 2016; Gottwald et al, 2017; Schumacher et al, 2017). Because the receptive fields of electrosensory receptors are spatially confined (Krahe and Maler, 2014), the lengths and spatial heterogeneity of the walls of refuges can have dramatic impacts on information encoded by each receptor and by downstream neural populations in the brain (Hofmann and Chacron, 2018). Electroreceptors can potentially encode such spatial structure, which the fish could use to determine its position within the refuge.…”
Section: Introductionmentioning
confidence: 99%